PENGARUH SUPERVISI AKADEMIK OLEH KEPALA SEKOLAH DAN PROGRAM PENGEMBANGAN TENAGA PENDIDIK TERHADAP KINERJA GURU TAMAN KANAK-KANAK GUGUS V KECAMATAN HARAUKABUPATEN LIMA PULUH KOTA - Karnedi, Devi Esisna, Antoni (MENARA EKONOMI, 2017)
This researchadopts thequantitative method with the causal design. It aimsto investigatetheimpactsof academic supervision and educatorsdevelopmentprogramson kindergartenteachers’ performance in Harau Lima Puluh Kota regency. The population of this researchis60 kindergarten teachers in the Harau sub-district. The data were collected fromMarchuntilApril 2016. The variables of theresearch areacademic supervision given by theheadmasters, educators development programs, and teachers’ performance. Based on theanalysis, someconclusionsare drawn:1) there aresignificant and positive impactsofacademic supervision by the headmastersonthe educators’ performance;the hypothesisisaccepted, 2) there areno significant impactsof educators’ development programs ontheteachers’ performance;the hypothesis isthen rejected, 3) academic supervision by theheadmasters and the educator development programs simultaneously affect the teachers’performance as indicated bythe probability value (sig) < 0,05. The research have someimplicationsonthe higher intensity of academic supervision in the learning process,observation, curriculum development, and professional development;the teacherswill havea better performance accordingly.Keywords: Academic Supervision, Educator Development, Teacher Performance.